İttihat ve Terakki dönemi Arnavut muhalefeti ve Arnavut ulusal hareketi - Sönmez, Banu İşlet, 1971- (My University, 2004)
Name and Surname: Banu İşlet Sönmez Field: Political Science and International Relations Program: International Relations Supervisor: Professor Cengiz Okman Degree Awarded and Date: Ph.D. - October 2004 Albanian National Movement, Albanian Opposition, Union and Progress

ALBANIAN OPPOSITION AND ALBANIAN NATIONAL MOVEMENT DURING THE PERIOD OF UNION AND PROGRESS Among the nationalisms that developed in the Balkan lands of the Ottoman Empire, Albanian nationalism has certain characteristics that are not shared by the nationalisms that developed among the Christian elements of the Empire. The factors that determine these special characteristics are the specific social conditions of the Albanians, their relations with the Ottoman administration and their position in the face of the international developments that shaped the destiny of the Ottoman Empire during the end of the 19th and the beginning of the 20th centuries. The aim of this study is to analyze the Albanian national movement during the Second Constitutional Period, within the context of its relation with the Ottoman administration and by taking into consideration the characteristics that separate Albanian nationalism from those that have developed among the Christian elements in the Balkans. The main focus of the study is the Ottoman state as the basic element forming the political context in which Albanian nationalism has developed. The scope of the study covers the period starting with the proclamation of the Second Constitution in 1908 and ending with the declaration of Albanian independence in 1912, which is the period in which Albanian nationalism has acquired a separatist tendency. Albanian opposition is treated as having two dimensions; first the conservative opposition that developed as a reaction to the break up of the traditional structure of the Ottoman Empire and the following centralizing measures of the administration, and second the progressive opposition that formed the core of the nationalist movement. Soyadı: Banu İşlet Sönmez yaset Bilimi ve Uluslararası İlişkiler Uluslararası İlişkiler Prof. Dr. Cengiz Okman Tez Türü ve Tarihi: Doktora - Ekim 2004 Arnavut Ulusal Hareketi, Arnavut Muhalefeti, İttihat ve Terakki ÖZET İTTİHAT VE TERAKKİ DÖNEMİ ARNAVUT MUHALEFETİ VE ARNAVUT ULUSAL HAREKETİ Osmanlı İmparatorluğu'nun Balkan topraklarında gelişen milliyetçilikler arasında Arnavut milliyetçiliğinin, Hıristiyan unsurlar arasında gelişen milliyetçiliklerden farklı bir konumu vardır. Bu konumu belirleyen etkenler Arnavutların kendilerine özgü toplumsal koşulları, Osmanlı yönetimi ile ilişkileri ve 19. yy.ın sonundan 20. yy.ın başına kadar olan dönemde Osmanlı İmparatorluğu'nun geleceğini belirleyen dış gelişmeler karşısındaki tutumlarıdır. Bu çalışmanın amacı, milliyetçi hareketlerin gelişimi açısından milliyetçi muhalefetle devlet yapısı ve yönetim arasındaki ilişki temel alınarak, Arnavut milliyetçi hareketini, İkinci Meşrutiyet Dönemi içerisinde, Osmanlı yönetimi ile olan ilişkileri çerçevesinde ve Arnavut milliyetçiliğini Balkanlar'daki Hıristiyan unsurlar arasında gelişen milliyetçiliklerden ayıran özellikleri de dikkate alarak çözümlemektir. Çalışmanın kapsadığı dönem İkinci Meşrutiyetin ilan edildiği 1908 yılından, Arnavutluk'un bağımsızlığının ilan edildiği 1912 yılına kadar olan süreçtir. Bu dönemin önemi, Arnavut milliyetçi hareketinin bu dönemle birlikte ayrılıkçı bir eğilim kazanmasından kaynaklanmaktadır. Arnavut muhalefeti, içerdiği iki boyut çerçevesinde ele alınmaktadır; birincisi Osmanlı İmparatorluğu'nun geleneksel yapısının çözülmesine ve bunu takip eden merkeziyetçi uygulamalara karşı bir tepki şeklinde gelişen muhafazakâr muhalefet ve ikincisi Arnavut ulusal hareketinin çekirdeğini oluşturan ilerici muhalefet.
Keywords: Türkiye_Tarih_Osmanlı İmparatorluğu_1299-1918